1980
DOI: 10.1111/j.1529-8817.1980.tb03019.x
|View full text |Cite
|
Sign up to set email alerts
|

BACTERIA INDUCED POLYMORPHISM IN AN AXENIC LABORATORY STRAIN OF ULVA LACTUCA (CHLOROPHYCEAE)1

Abstract: A laboratory culture of Ulva lactuca L. purified with antibiotics in 1958 can assume different morphologies. In synthetic media of the ASP type it grows as a pin‐cushion composed of uniseriate branching filaments. Only occasionally some finger‐like germlings appear which, after a few millimeters growth, disintegrate and originate the branched uniseriate filaments. Many strains of marine bacteria, isolated from Ulva and other seaweeds collected in nature or from laboratory cultures, when grown together with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
3

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 9 publications
4
104
0
3
Order By: Relevance
“…Although Bacteroidetes bacteria regulate morphogenetic processes in such diverse lineages as animals, red algae, and green algae (Provasoli and Pintner 1980; Matsuo et al 2005; Mazmanian et al 2005), the bacterially produced chemical cues that regulate most of these partnerships remain obscure. The limited phylogenetic distribution of bacteria capable of inducing rosette colony development suggested that A. machipongonensis and its close relatives may produce a characteristic molecule that could be identified biochemically.…”
Section: Resultsmentioning
confidence: 99%
“…Although Bacteroidetes bacteria regulate morphogenetic processes in such diverse lineages as animals, red algae, and green algae (Provasoli and Pintner 1980; Matsuo et al 2005; Mazmanian et al 2005), the bacterially produced chemical cues that regulate most of these partnerships remain obscure. The limited phylogenetic distribution of bacteria capable of inducing rosette colony development suggested that A. machipongonensis and its close relatives may produce a characteristic molecule that could be identified biochemically.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial interactions with algae in nature remain virtually unstudied, despite evidence from a number of laboratories that bacteria can have important consequences for algal growth and morphogenesis in culture (22,23,36,(39)(40)(41)45). Axenic cultures of marine macroalgae do not grow normally, a condition which can be alleviated by the readdition of any number of uncharacterized bacterial epiphytes or the maintenance of appropriate ratios of phytohormones (36,(39)(40)(41)45).…”
Section: Discussionmentioning
confidence: 99%
“…Axenic cultures of marine macroalgae do not grow normally, a condition which can be alleviated by the readdition of any number of uncharacterized bacterial epiphytes or the maintenance of appropriate ratios of phytohormones (36,(39)(40)(41)45).…”
Section: Discussionmentioning
confidence: 99%
“…By using CARD-FISH analysis we found that bacteria accounted for more than 90% of the cells in the microbial community over all four seasons. This is relatively high in comparison to the average of 56% determined in a review of FISH studies in aquatic environments (Bouvier and del Giorgio, 2003) and could be a reflection of the importance of bacteria for the normal morphological growth of Ulva (Provasoli and Pintner, 1980;Nakanishi et al, 1996;Matsuo et al, 2003). The larger non-hybridized cells observed frequently on the surface of U. australis are possibly diatoms and microalgae, which is in agreement with scanning electron micrographs-based observations of microfouling of small diatoms and blue-green algae on seaweed surfaces (Sieburth, 1975;Provasoli and Pintner, 1980;Dobretsov and Qian, 2002).…”
Section: ) and Coralsmentioning
confidence: 99%